PENINGKATAN AKTIVITAS BELAJAR DAN PEMAHAMAN KONSEP BIOLOGI SISWA MELALUI PENERAPAN MODEL GUIDED DISCOVERY DENGAN METODE CARD SORT DI KELAS XI IPA 3 MAN 1 PEKANBARU TAHUN PELAJARAN 2014/2015 - Enestasia Dewi Dewi; Wan Syafi’i syafi'i; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of  this research was to improve the learning activity and students' understanding of Biology concepts through the application of models Guided discovery with Card sort method in class XI IPA 3 MAN 1 Pekanbaru school year 2014/2015. This research is action research conducted in two cycles in March and April 2015. The subjects were students of class XI IPA 3 MAN 1 Pekanbaru school year 2014/2015, amounting to 32 people, consisting of 22 women and 10 men. Parameter research is learning activities and students' understanding of biology concepts consisting of absorption and mastery learning. The average of students' learning activities in the first cycle is 79.74% with sufficient category and the second cycle increased to 88.86% with the good category. Understanding the concept based on the average absorption of students in the first cycle is 80.94 and the second cycle increased to 88.06. Mastery learning students in the first cycle is 71.88% and the second cycle increased to 87.50%. From the results of this research concluded that the application of models Guided discovery with the Card sort method can increase the activity of learning and understanding the concept of class XI IPA 3 MAN 1 Pekanbaru school year 2014/2015. Keywords :  Model Guided discovery, Card sort method, Learning activity,  Understanding the concept of Biology.